Extracorporeal membrane oxygenation and left ventricular assist device: a case of double mechanical bridge - Kihara, S.; Kawai, Akihiko; Endo, Masahiro; Koyanagi, Hitoshi; Kurosawa, Hiromi (Heart and Vessels, 2002)
A 14-year-old boy with dilated cardiomyopathy with cardiac arrest was successfully implanted with a left ventricular assist device (LVAD) after 6-day extracorporeal membrane oxygenation (ECMO). He had multiple organ failure at the initiation of ECMO, but the failed organs recovered during assisted circulation, leading to LVAD implantation. This case showed the advantages of the "double bridge" such as: (1) quick and easy installation for acute cardiogenic shock, (2) providing intervention time for complications refractory to LVAD implantation, and (3) providing evaluation time for potential LVAD implantation and transplant candidates.